Terapi Rendam Kaki dengan Air Hangat terhadap Penurunan Tekanan Darah pada Ibu Hamil Preeklampsia - Banur Hadriyanti Rahayu; Fatma Jama; Munir, Nur Wahyuni (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2023)
Preeclampsia is a disease that is not contagious but can cause death in pregnant women. Preeclampsia can be treated with non-pharmacological methods, one of which is foot bath therapy with warm water. The purpose of this study was to determine the effect of foot soak therapy with warm water on reducing blood pressure in preeclamptic pregnant women at the North Galesong Public Health Center. This study is a quantitative study with a quasi-experimental design and a one group pretest-posttest design which was conducted on 37 preeclamptic pregnant women. The sampling technique used was purposive random sampling with a total sampling method that had been adjusted to the inclusion criteria and exclusion criteria. Bivariate analysis used the Wilcoxon test with a significance level of < 0.05. The results of this study indicate, before giving foot bath therapy with warm water to pre-eclamptic pregnant women there is mild and moderate preeclampsia blood pressure, after giving foot soak therapy with warm water to preeclamptic pregnant women there is normal and mild preeclampsia blood pressure, Wilcoxon test shows the pretest- posttest on blood pressure p Value = 0.000. The conclusion of this study is that there is an effect of giving foot soak therapy with warm water on blood pressure in pre-eclamptic pregnant women at the North Galesong Health Center. Therefore, warm water foot soak therapy can be used as a non-pharmacological therapy that can be done independently to reduce blood pressure in preeclamptic pregnant women.